Siantar Hotel: Silent Witness of the October 15, 1945 Bloody Event - Anita Siti M Gultom; Bunga Hidayati; Edo Bastian Silalahi; Rima Annisa Hanif; Sari Madani Rangkuti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to find out thoroughly about the Siantar Hotel which was a witness to the bloody incident on October 15, 1945 which left various kinds of relics and the meaning of these events among the community. The method used in this research is the historical method which includes 4 stages, namely heuristics, source criticism, interpretation and explanation. This study shows the findings; this event is a form of struggle of the Pematang Siantar people in fighting for and defending Indonesian independence against the Dutch soldiers who did not want independence and tried to disrupt the Pematang Siantar situation especially the incident regarding the Siantar Hotel Bloody incident was not widely known to the public so efforts were needed to introduce and disseminate it widely through learning local history about the struggle of the nation, especially in Pematang Siantar City, conducting shows or dramas about the 1945 Bloody Siantar Hotel in the community, and making the Siantar Hotel as a Cultural Heritage to be used as a source of learning for students and the younger generation today.